2020
DOI: 10.3390/ani10010099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Increasing Dietary Aminoacid Concentration in Late Gestation on Body Condition and Reproductive Performance of Hyperprolific Sows

Abstract: A total of 62 highly prolific Danbred sows was used to evaluate the implications of increasing dietary amino acid (AA) concentration during late gestation (from day 77 to 107 of pregnancy) on body condition and reproductive performances. Sows were assigned to one of the two treatments (n = 31, with similar number of sows in the second-, third- and fourth-cycle); control diet (containing 6 g of standardized ileal digestible lysine -SID Lys-)/kg) and high AA level (containing 10 g SID Lys/kg and following the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Inadequate provision of dietary Lys to gestating sows can result in fetal death, leading to stillbirths with mummies, which typically occur between day 60 and 100 of gestation, resulting in smaller total born piglets with a large number of mummies [ 25 – 27 ]. In the present study, accordingly, the litter mortality rate at birth quadratically decreased and total born piglets alive per litter quadratically increased with increasing dietary SID Lys, which agrees with Seoane et al [ 28 ] who found that multiparous sows consuming 10.0 g SID Lys/kg during the LG period (days 77 to 107) had a higher litter born alive compared to those consuming 6.0 g SID Lys/kg.…”
Section: Discussionsupporting
confidence: 92%
“…Inadequate provision of dietary Lys to gestating sows can result in fetal death, leading to stillbirths with mummies, which typically occur between day 60 and 100 of gestation, resulting in smaller total born piglets with a large number of mummies [ 25 – 27 ]. In the present study, accordingly, the litter mortality rate at birth quadratically decreased and total born piglets alive per litter quadratically increased with increasing dietary SID Lys, which agrees with Seoane et al [ 28 ] who found that multiparous sows consuming 10.0 g SID Lys/kg during the LG period (days 77 to 107) had a higher litter born alive compared to those consuming 6.0 g SID Lys/kg.…”
Section: Discussionsupporting
confidence: 92%
“…During late gestation, protein requirements of sows increase as compared to early gestation because of the nutritional support needed for fetal and mammary gland development [ 31 ]. A previous report shows that piglets with additional protein supplementation from the mother during the fetal phase are likely to be programmed for metabolizing high protein diets and are therefore more likely to more efficiently digest excessive amounts of dietary protein.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent reasons for culling include reproductive failure, lameness, aging, and reduced health, which affect the sow's reproductivity and longevity [2,3]. Most sows are culled immediately after weaning their last litter [4], when their physical condition is at its worst [5][6][7][8]. Even though most sows gain fat during pregnancy, they lose that reserve during lactation [7], as there is high energy demand.…”
Section: Introductionmentioning
confidence: 99%